2019
DOI: 10.1007/s00520-019-05200-6
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of using the Brief Pain Inventory in patients with cancer pain: an intervention study conducted in Swedish hospitals

Abstract: Purpose The prevalence of cancer pain is too high. There is a need for improvement of pain management in cancer care. The aim of this study was to explore whether the use of the multidimensional pain assessment questionnaire Brief Pain Inventory (BPI) could improve pain relief in hospitalized patients with cancer. Methods A controlled intervention study was performed at two hospitals in western Sweden, 264 patients were included, 132 formed a control group and 132 an intervention group. All participants comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…The HCP did not have access to the control group questionnaires. The study reported statistical signi cant improvement of symptoms on the follow up questionnaire compared with the baseline in the intervention group for almost all items of PPI and ESAS compared with the controlled group [22]. These results highlight the utility of symptom screening in routine clinical practice.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…The HCP did not have access to the control group questionnaires. The study reported statistical signi cant improvement of symptoms on the follow up questionnaire compared with the baseline in the intervention group for almost all items of PPI and ESAS compared with the controlled group [22]. These results highlight the utility of symptom screening in routine clinical practice.…”
Section: Discussionmentioning
confidence: 63%
“…The most common intervention was a treatment recommendation (12/32, 38%), such as an opioid prescription (Table 2). 4 [12] 7 [22] The higher median total ESAS-r score, indicating greater global symptom burden, was associated with higher rate of both documentation (p = 0.002) and intervention (p < 0.001). For individual symptoms, higher ESAS-r score was associated with signi cantly more documentation and intervention for both pain and tiredness only (p < 0.05) (Fig.…”
Section: Resultsmentioning
confidence: 96%
“…Therefore, the use of more elaborated multi-dimensional pain scales, such as Brief Pain Inventory would be in our view essential for future studies. 38 , 39 Indeed, management of HT-induced pain is multifactorial and the qualitative exploration of Galantino et al already indicated the importance of emerging themes, such as empowerment, community, sharing, and relieved stress. 40 …”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the use of more elaborated multi-dimensional pain scales, such as Brief Pain Inventory would be in our view essential for future studies. 38,39 Indeed, management of HT-induced pain is multifactorial and the qualitative exploration of Galantino et al already indicated the importance of emerging themes, such as empowerment, community, sharing, and relieved stress. 40 Although the study was not designed to compare effects of yoga practice among patients under AI or TM, as indicated in the results section, there were not statistical differences with nonparametric tests between 2 groups for any of parameters studied.…”
Section: Discussionmentioning
confidence: 99%
“…Sample size was calculated using data available from previous studies 11,13 This was calculated using 73% patients being symptoms free using the Kenalog protocol while another study showed at 2 weeks with conservative treatment, 11.7% 13 of patients were symptom free. The OpenEpi online software was used to calculate the sample size using these percentages, and a minimum sample size of 18 with the Fleiss method was calculated.…”
Section: Meth Odo Log Ymentioning
confidence: 99%